If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6p + -7)(7p + 6) = 0 Reorder the terms: (-7 + 6p)(7p + 6) = 0 Reorder the terms: (-7 + 6p)(6 + 7p) = 0 Multiply (-7 + 6p) * (6 + 7p) (-7(6 + 7p) + 6p * (6 + 7p)) = 0 ((6 * -7 + 7p * -7) + 6p * (6 + 7p)) = 0 ((-42 + -49p) + 6p * (6 + 7p)) = 0 (-42 + -49p + (6 * 6p + 7p * 6p)) = 0 (-42 + -49p + (36p + 42p2)) = 0 Combine like terms: -49p + 36p = -13p (-42 + -13p + 42p2) = 0 Solving -42 + -13p + 42p2 = 0 Solving for variable 'p'. Factor a trinomial. (-6 + -7p)(7 + -6p) = 0Subproblem 1
Set the factor '(-6 + -7p)' equal to zero and attempt to solve: Simplifying -6 + -7p = 0 Solving -6 + -7p = 0 Move all terms containing p to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -7p = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -7p = 0 + 6 -7p = 0 + 6 Combine like terms: 0 + 6 = 6 -7p = 6 Divide each side by '-7'. p = -0.8571428571 Simplifying p = -0.8571428571Subproblem 2
Set the factor '(7 + -6p)' equal to zero and attempt to solve: Simplifying 7 + -6p = 0 Solving 7 + -6p = 0 Move all terms containing p to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -6p = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -6p = 0 + -7 -6p = 0 + -7 Combine like terms: 0 + -7 = -7 -6p = -7 Divide each side by '-6'. p = 1.166666667 Simplifying p = 1.166666667Solution
p = {-0.8571428571, 1.166666667}
| 3y^2-y+1=0 | | 2(w-8)-5(w+4)=7-3w | | -10x-5x-10x=20-5x | | 13x+2=3(2x+1)-x+8 | | -x+3+9x=-3+2x+36 | | 2x^2=4-9x | | -19y=-76 | | -10-5x-10x=20-5x | | 7x+2+x=1+4x+13 | | 12x-1y=104 | | 7x+2x=1+4x+13 | | -10-5-10x=20-5x | | -3x-6=9 | | 9y-15=10 | | 9y-5=10 | | -7x+9=-4x-6 | | x-28+3x+20=537 | | -6a^2+8c^2+2a^2+11c^2= | | -5x+4y=-30 | | 3y=-2+6y | | 3x-7y=18 | | 2x*8x= | | (9k)-3=(8*9)+k | | -7xa-2xa-2ax-7ax= | | 20x(3x-28)=537 | | -6ay+8dz-4ya+2dz= | | 3by+4b+6by= | | -sy+6ys= | | 3b-2b= | | 3c+6c= | | (7+4)(4+-6)[(-4)-(-4)]= | | (7+4)(4+-6)(-4-4)= |